Predictors of future exacerbation risk in patients with asthma. Issue 7 (2nd October 2016) - Papaioannou, Andriana I.; Kostikas, Konstantinos; Bakakos, Petros; Papaporfyriou, Anastasia; Konstantellou, Elissavet; Hillas, Georgios; Papatheodorou, Georgios; Koulouris, Nikolaos G.; Papiris, Spyridon; Loukides, Stelios
ABSTRACT: Objectives : Although modern treatment of asthma improves asthma control, some patients still experience exacerbations. The aim of the present study was to detect predictors of asthmatic exacerbations Methods : We included patients with asthma followed up in asthma clinics of 2 tertiary University hospitals. Demographic and functional characteristics, levels of exhaled NO, and inflammatory biomarkers (IL-13, ΕCP και IL-8) and cell counts in induced sputum were recorded at baseline. Measurements were performed with the patients in stability and were considered as their personal best. Patients received optimal treatment with good compliance and were followed up for 1 year for asthma exacerbations occurrence. Evaluation of the effect of recorded parameters on asthma exacerbations was performed with univariate and multivariate Poisson regression analysis. Results : 171 patients (118 female) with bronchial asthma (mean age 51.6 ± 13.2 years) were included in the study. The mean number of exacerbations in 1 year of follow up was 0.4 ± 0.8 while the majority of patients (71.9%) did not experience any exacerbation. In multivariate Poisson Regression analysis only 3 characteristics were predictors of future exacerbations: FEV1 [IRR(95% CI)], [0.970(0.954–0.987)], p = 0.001, high BMI [1.078(1.030–1.129)], p = 0.001, and the need for permanent treatment with oral corticosteroids for asthma control maintenance [2.542(1.083–5.964)], p = 0.032 Conclusion : Optimal guideline-based asthma management results in minimal occurrence of exacerbations in the majority of patients. Predictors of exacerbations are low FEV1 levels in stability, high BMI and the need for permanent treatment with oral corticosteroids.